Ustadz Musgianto Rafiq's Da'wah Method in the Routine Study of PDAM Tirtanadi Employees on the Development of Tauhid Values and Islamic Work Ethics - Yohani Putri Dinar; Nashrillah (Global Writing Academica Researching and Publishing, 2026)
This study aims to analyze Ustadz Musgianto Rafiq's da'wah methods in routine studies of PDAM Tirtanadi employees and their impact on fostering the values ​​of monotheism and Islamic work ethic. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the da'wah methods used include lectures (bil-lisan), mau'izah hasanah, and interactive questions and answers. The material presented emphasizes strengthening monotheism and Islamic work ethic values ​​such as honesty, trustworthiness, and responsibility. These routine studies have a positive impact on increasing spiritual awareness and work motivation of employees within the company environment.